The cell polarity determinant Dlg1 facilitates epithelial invagination by promoting tissue-scale mechanical coordination. - Fuentes, M.A.; He, B. (Development, 2022)
Epithelial folding mediated by apical constriction serves as a fundamental mechanism to convert flat epithelial sheets into multilayered structures. It remains unknown whether additional mechanical inputs are required for apical constriction-mediated folding. Using Drosophila mesoderm invagination as a model, we identified an important role for the non-constricting, lateral mesodermal cells adjacent to the constriction domain ('flanking cells') in facilitating epithelial folding. We found that depletion of the basolateral determinant Dlg1 disrupts the transition between apical constriction and invagination without affecting the rate of apical constriction. Strikingly, the observed delay in invagination is associated with ineffective apical myosin contractions in the flanking cells that lead to overstretching of their apical domain. The defects in the flanking cells impede ventral-directed movement of the lateral ectoderm, suggesting reduced mechanical coupling between tissues. Specifically disrupting the flanking cells in wild-type embryos by laser ablation or optogenetic depletion of cortical actin is sufficient to delay the apical constriction-to-invagination transition. Our findings indicate that effective mesoderm invagination requires intact flanking cells and suggest a role for tissue-scale mechanical coupling during epithelial folding.